Sequential extraction procedure: a versatile tool for environmental research - Villén-Guzmán, María Dolores; Cerrillo-González, María del Mar; Paz-García, Juan Manuel; Vereda-Alonso, Carlos; Gómez-Lahoz, César; Rodríguez-Maroto, José Miguel (CISA publisher, 2020)
The sequential extraction procedure as a tool to assess the environmental risk of metals in solid matrices has been widely studied. In this work, other promising application of these methods is proposed: the evaluation of the recoverability of critical raw materials from a solid matrix. To this aim, the normalized sequential extraction procedure BCR was applied to a real contaminated soil from the south of Spain. In addition to this, the influence of the incomplete dissolution of carbonates contained in the soil on the fractionation results has been also studied. The high percentage of metal in the most mobile fractions suggested the potential use of the solid matrix as secondary source. The use of this approach together with environmental and economic feasibility studies would be an approach toward the circular economy
Keywords: Metales - Reciclado; Compuestos metálicos - Reciclado; Residuos - Aprovechamiento; Sequential extraction procedure; Metal recovery; Critical raw materials; Solid matrices; Circular economy